Islamic monetary instruments and msme financing in Indonesia: Empirical evidence for inclusive and sustainable growth - Nahdiyah Istiqomah (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Bank Indonesia as the monetary authority uses Islamic monetary instruments to promote inclusive financial access and real sector, especially Micro, Small, and Medium Enterprises (MSMEs) that are a significant part of the national economic resilience. Methods: This study uses monthly time-series data between January 2012 to December 2024 obtained through Bank Indonesia and Financial Services Authority (OJK) and implements the Vector Error Correction Model (VECM), and the Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) analysis. Findings: The IRF results indicate that PUAS and FASBIS have a stable and positive effect in MSME financing over time, SBIS has a small effect. In the meantime, the FEVD analysis proves that Islamic monetary instruments are significant determinants of changes in the financing of MSMEs. Such findings indicate the strategic effectiveness of the Islamic monetary policy towards inclusive and sustainable growth, particularly in the environment of digital transformation and economic uncertainty in the world. Conclusion: This paper concludes that out of the three Islamic monetary instruments studied; SBIS, PUAS, and FASBIS, only PUAS and FASBIS have a significant long-term impact on MSME financing in Indonesia with SBIS having no significant effect in the short or long run. Novelty/Originality of this article: The proposed study is expected to determine the efficacy of the Sharia-based instruments, SBIS, PUAS, and FASBIS in relaying the monetary policy through the MSME financing channel.